Dual nutrient heterogeneity modes in a continuous flow photobioreactor for optimum nitrogen assimilation to produce microalgal biodiesel - Leong, W.H. (Elsevier Ltd, 2022)
The impact of different nitrogen sources on the microalga, Chlorella vulgaris, was studied in a newly developed microalgal-bacterial photobioreactor via a dual nutrient heterogeneity mode. The mechanisms of nitrogen transformation and valorisation were unveiled, and subsequently, optimized via dual nutrient heterogeneity feeding modes comprising of various NH4+-N and NO3â-N concentrations. The nitrogen-assimilation mechanism from the microalgal-bacterial consortium was found to reduce microalgal growth inhibition, stemming at high NH4+-N concentrations. Accordingly, the total nitrogen removal efficiency was enhanced from 40.91 to 96.38 accompanied with maximum microalgal biomass production of up to 792 mg/L at a balanced or higher NH4+-N loading from mixed nitrogen environment. The harvested microalgal biomass contained high lipid accumulation of approximately 30 when fed with optimum NH4+-N and NO3â-N loadings at 60 and 58 mg/d, respectively. At this mixed nitrogen species loadings, high unsaturated fatty acid methyl esters (FAME) were attained. Indeed, the major FAME species (97â100) fell within the C16-18 range, signifying biodiesel characteristics conformity to the requirements for quality biodiesel application. Therefore, the dual heterogeneity modes of balanced NH4+-N and NO3â-N loadings into photobioreactor could offer effective microalgal nitrogen assimilation for sustainable wastewater treatment and microalgae-based biodiesel production simultaneously. Â© 2021 Elsevier Ltd